A NEW APPROACH TO CREATE SUSTAINED PONZI-LIKE SYSTEMS BY INCORPORATING PERPETUAL LIQUIDITY AND TIME EPOCHS - DUGULEANĂ Andreea Raluca; TĂNĂSESCU Cristina Roxana; DUGULEANĂ Mihai (Management of Sustainable Development)
This paper leverages the transformative capabilities of blockchain technology to introduce a new approach to developing Ponzi-like systems by integrating perpetual liquidity and time epochs within immutable smart contracts. Blockchain’s transparent nature establishes a foundation for trust in the ecosystem. Departing from the unsustainable nature and inevitable collapse associated with traditional Ponzi schemes, the proposed framework ensures continuous token availability, mitigating supply depletion and thus minimizing system failure risk. The introduction of time epochs is a key feature that enhances the sustainability of our system. It enables continuous rebalancing, predictability, and transparency within the system. Through predetermined intervals, users can claim a percentage of tokens from previous epochs, ensuring a fair distribution mechanism and preventing stagnation. This predictable cycle fosters the user’s confidence in the longevity of the protocol. The mechanics of the proposed system are designed to incentivize rational behaviour and trust among participants. Users are motivated to contribute to the ecosystem, knowing that their efforts will be reciprocated with proportional rewards. We design, implement and present the new model as a paradigm shift in Ponzi-like structures. Through a multidisciplinary lens encompassing economics, game theory, and sustainable development, this research aims towards fostering long-term viability and ethical financial practices.